The balancing of virtues—Muslim perspectives on palliative and end of life care: Empirical research analysing the perspectives of service users and providers. (30th November 2022) - Suleman, Mehrunisha
Abstract: In this paper, I will share findings from a qualitative study that offers a thematic analysis of 76 interviews with Muslim patients and families as well as doctors, nurses, allied health professionals, chaplains and community faith leaders across the United Kingdom. The data show that for many Muslims, Islam—its texts and lived practice—is of central importance when they are deliberating about death and dying . Central to these deliberations are virtues rooted within Islamic theology and ethics, the traditions of adab (virtue) and aqhlaq (proper conduct). Themes analysed include theological and moral understandings around the virtues of hope and acceptance. The study provides an analysis of these themes in relation to the experiences of Muslim patients and families arriving at meaning making around death and dying and how this interfaces with their interaction with biomedicine and healthcare. The study shows that the juxtaposition of different values and moral frameworks require careful negotiation when Muslim patients and families encounter the healthcare system. The study also describes how healthcare professionals and staff of other faiths and no faith encounter Muslim beliefs and practices, and the challenges they face in interpreting virtues and values rooted in faith, especially when these are perceived to be mutually opposed or inconsistent.